Internship Project with Groundwork Greater Nottingham To Establish a clear vision and formulate strategies towards that vision in order to position Ground work Nottingham in the competitive funding Environment. - Jawahar, Abbas Ansari (2008)
The transformation of the third sector from an obscure alternative to serve the society into a corporate business that does not seek profit has led to the necessity of adopting business tools like strategy, marketing and management. This issue has also triggered hot debates in the business world recently. The objective of this paper revolves around a charitable trust that is based in the east-midlands region in United Kingdom (Groundwork Greater Nottingham). The research intends to review the current position and operations of the organisation and its associated environments, in an objective to establish a clear vision and formulate strategies towards that vision in order to position the concerned Non profit organisation in the competitive funding environment. The exceptional growth of the third sector has triggered the non-profit organisation to adhere a more organised and structured attitude. The initial resistance that was thrust on business development tools like strategy, management and marketing are being slowly unveiled. This paper is an attempt to formulate strategies for a better positioning of Groundwork Greater Nottingham. The current position of the involved Non-profit organisation would be analysed in detail and presented in the form of a business case study. The paper would also try to argue on the importance of adopting strategy in the Non-profit sector and attempts to justify the same by an in depth industry analysis. The strategy formulation towards the identified vision would be with the help of a brief review of the guidelines from literature and identification of a framework that best suits the context. The strategy would be formulated with the help of identified analytical frameworks and the formulated strategy is also put under a process of evaluation to ensure its credibility. Critical arguments on the overall industry and the concerned organisation would also be discussed and further recommendations are given for the revival of the organisation to grow further. However, the challenges during the implementation of the formulated strategy are also another area which this paper aims to discuss briefly. Further, the paper also would recommend any additional research that would be needed for the purpose growing forward in the implementation of the strategies and going forward.